Advancements in CNC Machine System for Enhanced Part Development (International Journal of Innovative Research in Engineering & Management, 2023)
This paper presents a comprehensive  study on the part development of Aluminium-Silicon  Carbide (AlSiC) Particle Metal Matrix Composite  (MMC) using Computer Numerical Control (CNC)  machining. AlSiC MMCs have gained significant  attention due to their excellent mechanical properties and  thermal conductivity, making them suitable for various  applications in industries such as aerospace, automotive,  and electronics. The objective of this research is to  investigate the effects of CNC machining parameters,  such as cutting speed, feed rate, and depth of cut, on the  machinability and surface quality of AlSiC MMC parts.  Additionally, the paper aims to optimize the CNC  machining process to enhance the performance and  dimensional accuracy of the machined parts.
Keywords: Aluminium-Silicon Carbide (AlSiC) Particles; Metal Matrix Composite (MMC); Computer Numerical Control (CNC) Machines; Design of Experiments (DOE) etc